Potensi dan Aplikasi Diafiltrasi Pada Bidang Pangan, Perkebunan dan Peternakan - Aspriyanto A (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Today, various kinds of membrane-based separation technology regarded as a innovative breakthrough of chemical engineering have been widely invented, demonstrated, used industrially and commercialized to clarify, purify and concentrate wanted and valuable components in food and beverage, agricultural and farming, dairy, and animal product industries. Diafiltration (DF) is an operation mode of a pressure-driven filtrationapplied in hybrid with membrane-based separation in which fresh water or solute-free pure solvent or buffer as dialysate is added to the feed fluid and forced across the membrane together with salts, unwanted microsolutes and impurities. The main purpose of a DF process is to enhance the separation target of membrane-retained macrosolutes from membrane-permeable microsolutes and reduce as much salt, unwanted microsolutes and impurities in the feed fluid as possible. A principle cycle of DF step involves Ultrafiltration (UF) or Nanofiltration (NF) membrane to reduce fluid volumeand increase macrosolute concentration, DF processat constant volume to decrease microsolute concentration and fluid volume reduction to increase macrosolute concentration. The process of DF is discussed in connection with their applications in purification ofcane juice, purification of gelatin, recovery of whey and recovery of fermented mung beans